Profiles of High School Students' STEM Career Aspirations. Issue 3 (2nd September 2019) - Edwin, Mary; Prescod, Diandra J.; Bryan, Julia
Abstract : Science, technology, engineering, and mathematics (STEM) fields have a need for recruiting and retaining a diverse workforce. Understanding students' aspiration to STEM careers is important for supporting underrepresented populations. Data from a nationally representative sample ( N = 20, 010) of high school students who reported career aspirations were analyzed. Analyses revealed significant relations between students' aspirations and demographic variables, and differences in aspirations based on students' race and gender. Findings highlight a need for counselors to implement career interventions that address students' cultural contexts.